Optimum Fermentation Process for Red Macroalgae Gelidium latifolium and Gracillaria verrucosa - Mujizat Kawaroe; Dahlia Wulan Sari; Junkwon Hwangbo; Joko Santoso (Journal of Engineering and Technological Sciences, 2015)
Red macroalgae have the potential to be processed into bioethanol due to their high carbohydrate and low lignin content. Gelidium latifolium and Gracilaria verrucosa are red macroalgae commonly found in Indonesian seas. Sometimes an over-supply of red macroalgae is rejected by the food industry, which opens up opportunities for others uses, e.g. for producing bioethanol. The objectives of this research were to analyze the influence of sulfuric acid concentration on hydrolysis of G. latifolium and G. verrucosa and to calculate the optimum fermentation process to produce bioethanol. G. latifolium and G. verrucosa were hydrolyzed using H2SO4 at concentrations of 1%, 2%, 3%, and 4%, at a temperature of 121 °C and a pressure of 1.5 bar for 45 minutes. The process of fermentation was done using Saccharomyces cerevisiae in anaerobic conditions for 4, 5, 6 and 7 days. The results show that the optimum H2SO4 concentrations to hydrolyze G. latifolium and G. verrucosa were 1% and 2% respectively. The number of S. cerevisiae cells in hydrolysate G. latifolium and G. verrucosa increased in the third adaptation. S. cerevisiae can convert sugar from G. latifolium and G. verrucosa into bioethanol through fermentation. The highest bioethanol yields were achieved on days five and six. Therefore, red macroalgae can be seen as a potential raw material for bioethanol production.